Role Playing Method: A Solution To Improve Learning Outcomes In Islamic Education - Imam Tabroni; Rini Purnama Sari (IHSA Institute, 2023)
Whereas this research will be aimed at basic competency material regarding problems in learning knowledge of Islamic Religious Education. It can be seen that students' knowledge skills in learning Islamic Religious Education still lack understanding of the material. Students whose knowledge value is still below the KKM is approximately 40% of the 23 students. Most students do not understand the contents of the material, and the purpose of applying the material in everyday life. This study aims to improve student learning outcomes in learning Islamic Religious Education, and to find out the various obstacles in the application of the Role Playing method. This research is a classroom action research, which is conducted to solve problems in the classroom